2007
DOI: 10.1103/physrevc.76.065201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical coupled-channels model ofπNscattering in theW2GeV nucleon resonance region

Abstract: As a first step to analyze the electromagnetic meson production reactions in the nucleon resonance region, the parameters of the hadronic interactions of a dynamical coupled-channel model, developed in Physics Reports 439, 193 (2007), are determined by fitting the πN scattering data. The channels included in the calculations are πN , ηN and ππN which has π∆, ρN , and σN resonant components. The non-resonant meson-baryon interactions of the model are derived from a set of Lagrangians by using a unitary transfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
259
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(272 citation statements)
references
References 44 publications
10
259
3
Order By: Relevance
“…[8]. As a comparison, we also present the prediction of our early DCC model [2,10] (the green dotted curves), in which the amplitudes are unitary in the πN, ηN, and ππN(π∆, σN, ρN) channel space and are determined by analyzing the πN → πN scattering up to W = 2 GeV. Even without any adjustment of the model parameters to the πN → ππN data, our models reproduce the available total-cross-section data to better than ∼ 20% (∼ 60%) accuracy at W < 1.6 GeV (W > 1.6 GeV).…”
Section: Anl-osaka DCC Model For the πN → ππN Reactionmentioning
confidence: 99%
“…[8]. As a comparison, we also present the prediction of our early DCC model [2,10] (the green dotted curves), in which the amplitudes are unitary in the πN, ηN, and ππN(π∆, σN, ρN) channel space and are determined by analyzing the πN → πN scattering up to W = 2 GeV. Even without any adjustment of the model parameters to the πN → ππN data, our models reproduce the available total-cross-section data to better than ∼ 20% (∼ 60%) accuracy at W < 1.6 GeV (W > 1.6 GeV).…”
Section: Anl-osaka DCC Model For the πN → ππN Reactionmentioning
confidence: 99%
“…2.6 is solved in dynamical coupled-channel models which also take into account the dispersive parts from intermediate channels. Among those are the Sato-Lee model [70], which has been extended by the EBAC [71][72][73] and ANL/Osaka collaborations [74] and extensively applied to analyze pion photo-and electroproduction data. The Dubna-Mainz-Taiwan (DMT) [75,76], Valencia [77], Jülich-Bonn [78,79] and GSI models [80][81][82] have been developed along similar lines.…”
Section: Helicity Amplitudes Vs Transition Form Factorsmentioning
confidence: 99%
“…Figure 3 shows pole positions of P 11 N * resonances extracted from a dynamical model developed in Ref. [12]. Here, the poles A and B are well known as the double-pole (pole and shadow-pole [13]) structure of the Roper resonance with respect to the π∆ channel, which has been observed also in Refs.…”
Section: Multichannel Unitarity and Dynamical Coupled-channels Approamentioning
confidence: 78%
“…Then it was found that within the model developed in Ref. [12], all of the presented three P 11 resonance poles (the poles A, B, C) are generated from this single bare state as a result of its coupling to the multireaction channels [13]. This implies that a naïve one-to-one correspondence between the physical resonances and the baryons within static hadron models, within which the dynamical effects originating from coupling to the reaction channels are neglected, does not exist in general.…”
Section: Multichannel Unitarity and Dynamical Coupled-channels Approamentioning
confidence: 99%